Ground improvement acceptance criteria - Hamidi, Babak; Nikraz, Hamid; Varaksin, Serge (The Hong Kong Geotechnical Society and The Hong Kong Polytechnic University, 2011)
Once it has been established that ground improvement is required, a specification must be developed that defines the requirements of the works and the method that demonstrates that the works are acceptable. In some projects contractors are obliged to simply follow instructions and acceptance criteria are based on the quality of quantity of performed work. This method appears to be associated with the most amounts of risk and cost. Sometimes, acceptance criteria is based on minimum performance by specifying minimum acceptable test results. The ground improvement technique may or may not be specified. In this case, the associated risk and cost are less, but are still some drawbacks to this approach. Alternatively, acceptance criteria may be directly linked to design criteria. This method is associated with the least complications and will put the project at the minimal amount of risk.